Súcasný stav hrudnej chirurgie v SSR - Vrastyak, J; Klucár, J (Rozhledy v chirurgii, 1990)
The authors submit a report on the state of thoracic surgery in the Slovak Republic, based on the number and structure of thoracic surgical operations made in 1983-1987. Twenty departments were concerned with thoracic surgery and 21 surgeons had the qualification of thoracic surgeons. The authors mention only briefly problems pertaining to the organization of the discipline.
Keywords: Workforce; zdravotnická zařízení; Health Facilities; Československo; Thoracic Surgery; Humans; lidé; hrudní chirurgie; pracovní síly; Czechoslovakia